Phase analysis of chromium (III) oxide and aluminium oxide using x-ray diffraction / Surul Huda Din - Din, Surul Huda (2010)
X-Ray powder diffraction is an advanced technique primarily used for phase identification and determination of the structure of crystalline material. Cr₂O₃ and A1₂O₃ are used as samples of study in this thesis. Cr₂O₃ has been synthesized first from chromium (III) nitrate using sol-gel method while A1₂O₃ has been synthesized from aluminum acetate using same method. The samples of Cr₂C₃ then heated at 400°C for 4 hours and 700°C for 12 hours. The annealing temperature for AI2O3 was 1300°Cfor48 hours. The samples then subjected to characterization process using X-Ray powder diffraction. The powder patterns then can be search match using X'Pert HighScorePlus software. The results showed Cr203 has higher purity and crystallinity at 700°C and A1₂O₃ pure at 1300°C.